Hubungan Karakteristik dengan Status Gizi Lanjut Usia di Pekon Parerejo Kecamatan Gadingrejo Kabupaten Pringsewu - Erviani, Annisa Septy; Abdullah; Khairani, Masayu Dian; Muharramah, Alifiyanti (Jurnal Gizi Aisyah, 2024)
The problem of malnutrition in the elderly is easily seen through general appearance. The purpose of this study was to determine the relationship between characteristics and nutritional status of the elderly in Pekon Parerejo, Gadingrejo District, Pringsewu Regency. This research method uses analytic quantitative research using a cross-sectional approach. The population in this study were 65 elderly people with a sample size of 50 respondents selected by purposive sampling. Data analysis using chi square test and gamma test. The results showed that nutritional status was thin 24 (48.0%) respondents, very thin 7 (14.0%) respondents and obese 4 (8.0%) respondents. Female gender was 33 (66.6%) respondents and male 17 (34.0%) respondents. The age of respondents was 45-55 years (52.0%) and 56-59 years (48.0%), while the education level of respondents was elementary school (84.6%), junior high school (10.0%) and high school (6%). The results showed that the nutritional status of thin 24 (48.0%) respondents, very thin 7 (14.0%) respondents and obese 4 (8.0%) respondents. Female gender was 33 (66.6%) respondents and male 17 (34.0%) respondents. The age of respondents was 45-55 years (52.0%) and 56-59 years (48.0%), while the education level of respondents was elementary school (84.6%), junior high school (10.0%) and high school (6%). The results of statistical analysis showed there was no relationship between age and nutritional status, p-value = 0.125 (p-value >α = 0.05), there was a significant relationship between gender and nutritional status, p-value = 0.001 (p-value <α = 0.05), and there was no relationship between education level and nutritional status, p-value = 0.151 (p-value >α = 0.05).